(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
B. F. Skinner’s Verbal Behavior is the foundation for understanding language and communication within Behavior Analysis. The Verbal Behavior Developmental Theory (VBDT) is a growing body of empirical research that builds upon and expands this foundation, incorporating the Naming Theory and the Relational Frame Theory (RFT). VBDT identifies and organizes language development milestones into a trajectory of behavioral cusps and cusps that are new learning capabilities to create a comprehensive understanding of how individuals learn language. Specific instructional histories lead to the acquisition of new conditioned reinforcers, thus new cusps and capabilities emerge. Not only does VBDT identify and describe such milestones, but it also includes specific research-based protocols for inducing cusps and capabilities which could solve learning problems. This paper describes each cusp and capability as they have been identified in the research thus far and summarizes the basic principles and concepts from which they were derived.